2007
DOI: 10.1299/jtst.2.123
|View full text |Cite
|
Sign up to set email alerts
|

Feasible Optimal Design of High Temperature Vacuum Furnace Using Experiences and Thermal Analysis Database

Abstract: A new method using thermal analysis database and optimization technique has been developed to substitute the original method what was based on trial and error. First, an original vacuum furnace was manufactured according to experiences. Modified baseline vacuum furnace which can be used in high temperature was produced from the original one by using experimental data and experiences. The results in 2 different conditions of nearly vacuum and argon ambient gas were investigated in order to define the worse but … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2008
2008
2011
2011

Publication Types

Select...
3
3

Relationship

4
2

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 3 publications
0
11
0
Order By: Relevance
“…For improving the accuracy, different profiles were used for upper and lower surfaces. In this study, SQP(sequential quadratic programming) optimization algorithm was used [4,8,9].…”
Section: A Formulation and Optimal Resultsmentioning
confidence: 99%
“…For improving the accuracy, different profiles were used for upper and lower surfaces. In this study, SQP(sequential quadratic programming) optimization algorithm was used [4,8,9].…”
Section: A Formulation and Optimal Resultsmentioning
confidence: 99%
“…(2). W is the weighting factor, q original is required heat of original vacuum furnace described in a previous study and V original is volume of the insulator which can be expressed by design variables [4]. (1 ) original original…”
Section: Optimal Results Using Response Surface Methodsmentioning
confidence: 99%
“…In this study, a new method based on the response surface method and optimization technique has been developed which can be used to design a high temperature vacuum furnace. At first, thermal analysis was carried out for constructing the response surface under the condition of using the calculated thermal conductivity of the insulator in a previous study [4]. In the process of constructing the response surface, the D-optimal method was used to select experimental points.…”
Section: Introductionmentioning
confidence: 99%
“…The user's requirement was set that the large scale vacuum furnace is operated at 1650 under the condtion of having argon ambient gas. Heat transfer in a large scale vacuum furnace mainly includes conduction heat transfer and radiation heat transfer, and natural convection must be considered when ambient gas is used in heat treatment [5][6][7][8]. In order to carry out thermal analysis of the large scale vacuum furnace, CFD-ACE [9] analysis code which based on finite volume method was used.…”
Section: Introductionmentioning
confidence: 99%
“…In order to carry out the thermal analysis of the large scale vacuum furnace, the thermal conductivity of the insulator must be known. In this study, the thermal conductivity of the insulator was interpolated using the data shown in Table 1, and the heater in a previous study was used [5]. Fig.…”
Section: Introductionmentioning
confidence: 99%